Intrauterine balloon tamponade in the management of severe postpartum haemorrhage after vaginal delivery: Is the failure early predictable?. (March 2021) - Leleu, A.; Ghesquiere, L.; Machuron, F.; Caudrelier, C.; Devouge, P.; Subtil, D.; Houflin-Debarge, V.; Garabedian, C.
Highlights: IUBT is essential and effective in the management of PPH. Rapid, massive haemorrhages with coagulopathy are failure factors of IUBT. Blood loss at 10 min is good factor prognostic of early IUBT failure. At 10 mn after IUBT, blood loss greater than 250 mL should consider invasive procedure. Abstract: Postpartum haemorrhage (PPH) is one of the leading causes of maternal morbidity and mortality world-wide. The arrival of intrauterine balloon devices has revolutionised PPH management. However, it seems interesting to know the situations of failure to improve the management. The objective is to define the factors related to failure of intrauterine balloon tamponade (IUBT) in women with a postpartum haemorrhage (PPH) after vaginal delivery, and especially blood loss after placement to avoid delaying management. Retrospective cohort study was conducted in 2 centers. All PPH after vaginal deliveries treated by IUBT were included. Two groups were defined (successes and failures) and compared. Failure was defined as the need of invasive procedure. Calculated area under receiver operating characteristic (ROC) curves and thresholds of bleeding at 10 min were also calculated for prediction of failure. 127 women were included. The overall success rate was 78.0 % (95 % CI 70.7–85.1 %). Blood loss at 10 min was factor prognostic of early IUBT failure. The ROC curve of blood loss at 10 min for prediction of failure of IUBT had an area under the curve of 0.876 (95 % CI 0.782–0.970). The predictive positive value of blood loss at 10 min were respectively 0.53, 0.8 and 0.94 for blood loss of 100, 200 and 250 mL. Physicians should be alerted if blood loss are more than 200 mL at 10 min after placement of IUBT and considered invasive procedure if more than 250 mL to avoid delaying management of PPH.